Endocrine disorders and the neurologic manifestations - Jeesuk Yu (Korean Society of Pediatric Endocrinology, 2014)
The nervous system and the endocrine system are closely interrelated and both involved intimately in maintaining homeostasis. Endocrine dysfunctions may lead to various neurologic manifestations such as headache, myopathy, and acute encephalopathy including coma. It is important to recognize the neurologic signs and symptoms caused by the endocrine disorders while managing endocrine disorders. This article provides an overview of the neurologic manifestations found in various endocrine disorders that affect pediatric patients. It is valuable to think about 'endocrine disorder' as a cause of the neurologic manifestations. Early diagnosis and treatment of hormonal imbalance can rapidly relieve the neurologic symptoms. Better understanding of the interaction between the endocrine system and the nervous system, combined with the knowledge about the pathophysiology of the neurologic manifestations presented in the endocrine disorders might allow earlier diagnosis and better treatment of the endocrine disorders.